Is Saccharomyces cerevisiae azoreductase the plasma membrane ferric reductase? - Ramalho, Patrícia Alexandra Costa Ferreira (2004)
Poster apresentado na International Conference on Plasma Membrane Redox Systems and their Role in Biological Stress and Disease, 7, Asilomar, Califórnia, Estados Unidos da América, 14-18 Abril 2004.